The Efficacy and Safety of Dexamethasone Intravitreal Implant for Diabetic Macular Edema and Macular Edema Secondary to Retinal Vein Occlusion: A Meta-Analysis of Randomized Controlled Trials - Li Xiaodong; Xie Xuejun (Journal of Ophthalmology)
Purpose. The purpose of this meta-analysis was to evaluate the efficacy and safety of dexamethasone intravitreal implant (DEX) for the treatment of diabetic macular edema (DME) with retinal vein occlusion secondary to macular edema (RVO-ME). Materials and Methods. Relevant databases were searched to include randomized controlled trials (RCTs) evaluating DEX for DME and RVO-ME. The search was conducted until March 2022. Meta-analysis was performed using Rev Man 5.4.1 software after screening the literature by inclusion and exclusion criteria, extracting information, and evaluating the methodological quality of the included studies. Results. The study showed that DEX treatment of RVO-ME was associated with an improvement in best corrected visual acuity (BCVA) (MD = −9.08, 95% CI: −10.89–7.27, P<0.00001) and central retinal thickness (CRT) (MD = 93.47, 95% CI: 28.55–159.39, P=0.005). DEX treatment of DME was significantly better than anti-VEGF treatment in terms of CRT reduction (MD = −72.35, 95% CI: −115.0–29.69, P=0.0009). The safety study showed that the risk of cataract from RVO-ME (OR = 5.06, 95% CI: 1.96 to 13.06, P=0.0008) and the incidence of high intraocular pressure (OR = 6.67, 95% CI: 3.46 to 12.86, P<0.00001) were significantly higher with DEX than with anti-VEGF therapy. The risk of cataract from DME (OR = 4.70, 95% CI: 2.10 to 10.54, P=0.00022) was significantly higher with DEX than with anti-VEGF therapy (OR = 4.70, 95% CI: 2.10 to 10.54, P=0.0002). The incidence of high IOP (OR = 13.77, 95% CI: 4.96 to 38.18, P<0.00001) was significantly higher with DEX than with anti-VEGF therapy. Conclusions. In patients with DME and RVO-ME, DEX was more efficacious but slightly less safe than anti-VEGF therapy.